A política desenvolvimentista do Partido dos Trabalhadores: 2003/2010 - Morais, Marcelo Maurício de (2021)
This thesis addresses the developmental Policy of the 2000s in the Lula governments and focuses its analysis on the institutional aspects of the policy. In this sense, the research approaches the economy from a political perspective. Specifically, it seeks to understand how the "developmentalist project" of the Workers' Party has expanded and strengthened since 2007. The basic line will be guided by the study of the nature of the developmentalist experience initiated by the Lula government which, in turn, begins a project characterized by contradictions arising from the "class conciliation" within the power bloc. It is assumed, therefore, that both the Lula administration and the Workers' Party should reach the end of their second term with a project that is very close to a developmental project. The analyses focused on the politicalideological aspects that led the Workers' Party to take this path, as well as on the economic perspectives idealized so that the expedient would be paved for the effective realization of the "developmentalist project". Its economic policy, public policies, institutional changes as a mechanism to facilitate the implementation of such a project; its foreign policy, the strategic sectors of the economy, and the BNDES' role as the main driver to trigger economic acceleration, as well as the country's own development, in addition to the distributional issue, a major part of any development project